Synergistic Catalytic Effects on Nitrogen Transformation during Biomass Pyrolysis: A Focus on Proline as a Model Compound - Shan Cheng; Kehui Yao; Hong Tian; Ting Yang; Lianghui Chen (Molecules, 2024)
To investigate the control mechanisms of NOx precursors and the synergistic effects of composite catalysts during proline pyrolysis, a systematic series of experiments was conducted utilizing composite catalysts with varying Fe-Ca ratios. Product distribution analysis was employed to elucidate the catalysts’ mechanisms in reducing NOx precursor emissions. The synergistic interactions between Fe and Ca were quantitatively assessed through comparative theoretical and experimental release calculations. The results indicate that an increase in the Fe content in the catalyst led to a rise in amine concentrations from 0.9% to 2.95%, implying that Fe facilitates the generation of amine-N through ring-opening and substitution reactions. When the Fe to Ca ratio was balanced at 1:1, nitrogen predominantly participated in the formation of purines via cyclization and substitution reactions. Additionally, all composite catalysts exhibited a suppressive effect on the release of NOx precursors, attributed to their significant enhancement of solid product retention. Fe-Ca composite catalyst synergistically inhibits the release of gaseous nitrogen. Notably, the strongest synergistic effect was observed with a 1:3 Fe to Ca ratio, which reduced the release of NH3 by 38.7% and HCN by 53.6% during proline pyrolysis. This study offers valuable insights into the control of NOx precursors and the optimization of nitrogen-rich biomass pyrolysis processes.